Exploring the Concept of Ethnomathematics in the Decorative Varieties of Balinese Endek Woven Cloth - Rahmadhani, Serly Nur; Wijaya, Cecilia Celina; Srinadi, I Gusti Ayu Made (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This study aims to explore the ethnomathematical concept embedded in the decorative patterns of Balinese Endek woven fabric through an analysis of its motifs, production processes, and the mathematical meanings represented by the artisans. The research employed a qualitative ethnographic approach conducted at Endek Sekar Jepun in Denpasar. Data were collected through participatory observation, in-depth interviews, and visual documentation of motifs and weaving processes using traditional non-machine looms (ATBM). The results show that Endek decorative patterns are composed of basic geometric shapes such as rhombuses, triangles, squares, and organic curves resembling bamboo shoots. These motifs apply mathematical concepts including symmetry, pattern repetition, proportion, and scale, which reflect order, balance, and the symbolic meanings of Balinese culture. The artisans’ weaving practices demonstrate intuitive applications of mathematical principles, serving as concrete examples of ethnomathematical practice. These findings have implications for culturally grounded mathematics education, the development of contextual learning materials, and the preservation of Balinese cultural heritage through systematic documentation of Endek motifs